WE-AB-202-10: Modelling individual tumor-specific control probability for hypoxia in rectal cancer. - Warren, S; Warren, D; Wilson, J; Muirhead, R; Hawkins, M; Maughan, T; Partridge, M (Wiley, 2016)
To investigate hypoxia-guided dose-boosting for increased tumour control and improved normal tissue sparing using FMISO-PET images